Pelatihan Pembuatan Sabun Lembaran Berbahan Aktif Kulit Buah Naga di Panti Asuhan Izzati Jannah - Fathnur Sani K.; Yuliawati Yuliawati; Elisma Elisma; Syamsurizal Syamsurizal; Muhammad Syukri (Poltekita: Jurnal Pengabdian Masyarakat, 2023)
In recent years, the world has been shocked by the emergence of a disease caused by a virus, namely the corona virus or better known as COVID-19. The rapid spread of Covid-19 requires precautions to prevent transmission to break the chain of the COVID-19 pandemic and be able to face the new normal era. One of the preventive measures is to carry out the movement of washing hands with soap. Sheet soap is used as disposable hand soap and is perfect for use when traveling or doing activities outside the home. Currently, the community has started to carry out offline school and lecture activities. This activity aims to demand awareness to increase activities that are able to prevent the spread of Covid-19. So bringing antiseptic products, both in the form of liquids and sheet soap, is highly recommended to provide comfort in dealing with the new normal conditions after the Covid-19 pandemic. Activity method: This activity is planned to be carried out at the izzati jannah orphanage where the orphanage students have carried out learning activities offline. Activities are carried out following strict health protocols. The counseling activity was attended by 30 orphanage children. Based on the results of the post test, it was obtained a value of 92% of students being able to understand the training material provided. So that the results of the activity show that there is an increase in the knowledge of the orphans about processing dragon fruit peel powder into sheet soap that is easy to use and carry.